ENHANCING ISLAMIC BUSINESS ETHIC OF INSURANCE UNDERSTANDING TOWARDSHIGH QUALITY FINANCIAL ADVICE AMONGSTTAKAFUL AGENTS - Azmin, Adi Anuar; Bakar, Azizi Abu; Ghani, Abdullah Hj. Abd; Kadir, Hanita (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2015)
In modern business, one way to reduce risk of damage caused by accidents, illness, ordeath is through insurance. This concept does not necessarily contradict with Islamic principle as it also highlights the importance of high moral standing and high ethics level practiced by individuals. In particular, for insurance agents who have better positions in havingpersonal contacts with consumers, Cooper and Frank (1990) argue that the key ethical problem for agents was due to lack of knowledge or skills to competently perform one's duties as well as conflicts of interests between their duties andopportunities for personal financial gain. A Malaysianstudy by Mohamad and Mohd (2009) revealed that Takaful agents are the major source of information to create awareness. However, the basic concept of Takafulis still very ambiguous among Takaful agents, thus, it would influence the quality of advice delivered to customers.The role of Takaful agents is undeniable especially during the recent enforcement of Islamic Financial Services Act (IFSA 2013), introduced by Malaysian government. The enforcement whichrequires Islamic financial institutions to fully comply toShariaprinciples would mostly affectthe Takaful and conventional market.One of the Shariaprinciples is transparency. The new legislations thus enhance the level of confidence among stakeholders. The concept paper attempts to embark the role of Islamic business practice indetermining financial advice among Takaful agents. If they fully appreciate the Takafulconcept, the financial advice to customers could be improved which will gradually boost the Malaysian Takaful industry in the long run.